Aktivitas In Vitro Penurun Gula Darah dari Ekstrak Buah Parijoto (Medinilla speciosa B.) - Vifta, Rissa; Wilantika, NFN; Advistasari, Yustisia Dian (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
Diabetes mellitus is one of the highest causes of death in the world, with symptoms of increased blood glucose levels (hyperglycemia). One of the efforts made as a treatment and prevention of DM is through complementary therapy using natural ingredients. Parijoto fruit (Medinilla speciosa) contains flavonoid compounds potential to reduce glucose levels. The study aimed to analyze the effectiveness of ethanol extracts and its fractions of parijoto fruit (EEBP) to decrease glucose levels in vitro. The study was conducted at the Ngudi Waluyo University Laboratory in April to August 2018. Identification and screening of flavonoid compounds from ethanol extracts and its fractions of parijoto fruit were performed qualitatively and by thin-layer chromatography (TLC). In vitro testing for Â antidiabetic activity of EEBP was performed with non-enzymatic reaction by Nelson Somogyi method (ethanol extract and its fractions). Experiment Â was arranged in a randomized block design, with 12 treatments and three replications. The concentrations of parijoto fruit tested were 10 ppm, 20 ppm, 30 ppm, 40 ppm, 50 ppm, and 60 ppm. The results of qualitative identification and TLC showed that the ethanol extract and its fraction of EEBP contained flavonoid compounds. At a concentration of 30 ppm, EEBP was able to reduce glucose levels by 42.43 %, while the ethanol fraction decreased glucose levels by 83.38 %. The results showed parijoto fruit ethanol extract and its fractions were sources of antidiabetic. Hence its pharmacologically effect was necessary to be further studied.